Disseminated tumor cells are not associated with established risk factors, L1CAM immunoreactivity and outcome in endometrial carcinoma - Kommoss, Stefan; Wallwiener, Markus (Journal of cancer research and clinical oncology, 2017)
PurposeThe presence of disseminated tumor cells (DTC) in the bone marrow of endometrial carcinoma patients has been demonstrated previously. In contrast to breast cancer, no prognostic significance or association with clinicopathological features was revealed for endometrial carcinoma so far. The aim of this study was to investigate DTC in a large patient cohort with in-depth pathology review data available and to study DTC occurrence in the context of L1CAM and long-term disease specific follow-up.MethodsPatients treated for endometrial carcinoma at the Tuebingen University Women’s hospital between 2003 and 2013 were identified. Cases with previous expert central pathology review including L1CAM immunohistochemistry and bone marrow aspirates available were selected. The presence of DTC and L1CAM expression was studied immunohistochemically.ResultsIn 395 cases with a confirmed diagnosis of endometrial carcinoma, bone marrow aspirates were available. DTC were detected in 17.2%. The presence of DTC was independent from tumor histology, grade, lymphovascular space involvement (LVSI), FIGO stage, myoinvasion, L1CAM immunoreactivity, and nodal metastasis. DTC occurred less frequently in cases with a microcystic elongated and fragmented (MELF) pattern of invasion (2.2 vs. 21.8%, p = 0.0003). Disease progression was distributed equally among patients with and without DTC present.ConclusionsWe were able to confirm previous findings of DTC presence in a large well-characterized cohort of endometrial carcinoma patients. DTC are detectable in almost one-fifth of endometrial carcinoma and occur less frequently with a MELF pattern of invasion. Further studies investigating the role of DTC in endometrial carcinoma are warranted.
Gesehen am 12.11.2018